2013
DOI: 10.1007/s00446-013-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

No sublogarithmic-time approximation scheme for bipartite vertex cover

Abstract: König's theorem states that on bipartite graphs the size of a maximum matching equals the size of a minimum vertex cover. It is known from prior work that for every ε > 0 there exists a constant-time distributed algorithm that finds a (1 + ε)-approximation of a maximum matching on bounded-degree graphs. In this work, we show-somewhat surprisingly-that no sublogarithmic-time approximation scheme exists for the dual problem: there is a constant δ > 0 so that no randomised distributed algorithm with running time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…They show that even for bipartite graphs of maximum degree 3, there exists a contant ε 0 > 0 such that any randomized distributed (1 + ε 0 )-approximation algorithm for the (unweighted) minimum vertex cover problem requires Ω(log n) rounds. As our last contribution, we generalize the result of [GS14] to computing (1 + ε)-approximate solutions for any sufficiently small ε > 0.…”
Section: Our Contributionsmentioning
confidence: 97%
See 4 more Smart Citations
“…They show that even for bipartite graphs of maximum degree 3, there exists a contant ε 0 > 0 such that any randomized distributed (1 + ε 0 )-approximation algorithm for the (unweighted) minimum vertex cover problem requires Ω(log n) rounds. As our last contribution, we generalize the result of [GS14] to computing (1 + ε)-approximate solutions for any sufficiently small ε > 0.…”
Section: Our Contributionsmentioning
confidence: 97%
“…For unweighted matchings, a round complexity that is completely independent of n was obtained by [BCGS17]. Interestingly, Göös and Suomela in [GS14] showed that such a result is not possible for the minimum vertex cover problem, even in the LOCAL model. They show that even for bipartite graphs of maximum degree 3, there exists a contant ε 0 > 0 such that any randomized distributed (1 + ε 0 )-approximation algorithm for the (unweighted) minimum vertex cover problem requires Ω(log n) rounds.…”
Section: Our Contributionsmentioning
confidence: 99%
See 3 more Smart Citations